2007
DOI: 10.1038/ng1970
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial bottleneck occurs without reduction of mtDNA content in female mouse germ cells

Abstract: Observations of rapid shifts in mitochondrial DNA (mtDNA) variants between generations prompted the creation of the bottleneck theory. A prevalent hypothesis is that a massive reduction in mtDNA content during early oogenesis leads to the bottleneck. To test this, we estimated the mtDNA copy number in single germline cells and in single somatic cells of early embryos in mice. Primordial germ cells (PGCs) show consistent, moderate mtDNA copy numbers across developmental stages, whereas primary oocytes demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
285
1
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(319 citation statements)
references
References 28 publications
23
285
1
10
Order By: Relevance
“…As for mammalian embryogenesis (Cao et al, 2007), the mtDNA content of teleost oocytes is believed to remain constant during early embryogenesis, and mitochondria present in the oocyte are apportioned to the cells of the developing embryo with the majority assigned to extraembryonic tissues (Fleming et al, 1992;Dumollard et al, 2007a). Thus, a genetic bottleneck comparable to that described for mammalian embryogenesis is expected in teleosts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As for mammalian embryogenesis (Cao et al, 2007), the mtDNA content of teleost oocytes is believed to remain constant during early embryogenesis, and mitochondria present in the oocyte are apportioned to the cells of the developing embryo with the majority assigned to extraembryonic tissues (Fleming et al, 1992;Dumollard et al, 2007a). Thus, a genetic bottleneck comparable to that described for mammalian embryogenesis is expected in teleosts.…”
Section: Discussionmentioning
confidence: 98%
“…However, this ratio does not necessarily reflect the extent of paternal leakage in the developing embryo. The mtDNA content remains constant during early embryogenesis (Cao et al, 2007;Cree et al, 2008) and mitochondria are apportioned to arising cells in a random fashion. Because most of these cells form extraembryonic tissues (Hogan et al, 1986), only a subset of all cells and consequently mtDNAs present in the zygote will ultimately contribute to the embryo proper (Fleming et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, the vast majority of sexually reproducing organisms have uniparental transmission of mtDNA [8,44], maintaining high relatedness. Furthermore, regular single-celled bottlenecks, usually in combination with an additional bottleneck for mtDNA [9,10], facilitate efficient selection against suppressive mtDNA.…”
Section: (D) Mtdna Evolution In Other Organismsmentioning
confidence: 99%
“…Furthermore, an mtDNA bottleneck during egg cell formation has been shown in mice [9][10][11], redistributing mtDNA variation from within cells to among cells, and facilitating selection among individuals [12], as well as purifying selection in the germline [13]. A unifying characteristic of these different mechanisms is that they increase the genetic relatedness among the mtDNAs within individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The number of mitochondria in an oocyte can be estimated by analysis of mtDNA copy number because oocytes contain only one to two mtDNA copies per mitochondrion (Pikó and Matsumoto 1976;Pikó and Taylor 1987;Jansen 2000;Santos et al 2006b;Jiao et al 2007;Chiaratti and Meirelles 2010). For successful early embryonic development, a species-specific minimum number of mitochondria appears to be required; for example, mouse oocytes are thought to require at least 50 000-200 000 mtDNA copies (Cao et al 2007;Cree et al 2008;Wai et al 2008Wai et al , 2010, whereas bovine, porcine and human oocytes have been reported to require between 100 000 and 700 000 mtDNA copies if they are to retain developmental competence (Steuerwald et al 2000;Reynier et al 2001;May-Panloup et al 2005a;Almeida-Santos et al 2006b;Spikings et al 2007;Zeng et al 2007). However, during early embryonic development, mtDNA replication is transiently arrested (St. John et al 2010) and therefore the mtDNA copy number either remains constant (e.g.…”
Section: Introductionmentioning
confidence: 99%